Blockchain-based secure medical record sharing system - Tian, Xiang Yang (2019)

(untitled)
Database storage is a traditional way to keep all the data on a central database server. It may keep data expose in integrity issue and accuracy problem especially for the medical sector. Blockchain as a popular topic nowadays, it is able to ensure data security while using the distributed topology. The data is also protected by only allowed the permissioned personnel whom granted access by Blockchain. The main issue of medical institutions is the synchronization of patients’ data. Each medical institutions have their own database, but the patients may not go to a specific clinic every time. Therefore, it is difficult to get the updated record of patient in order to provide the diagnosis accurately. The another problem is the research institution difficult to obtain the medical record for research purpose from medical institution due to the privacy issue. In this project, the framework of Blockchain 3.0 Hyperledger Fabric will be implemented to solve the problem stated above. The Hyperledger Composer will be used to setup the development environment, running environment and playground for running the Blockchain. Besides that, Channel and Chaincode will be used in this system. At the end of project, a system will be designed for the usage of medical and research institution. Patients are able to use mobile application to view their medical records. In addition, the medical records are able to update by medical institution and view by permissioned research institution through web application.